Assembly Line Efficiency Improvement by Using WITNESS Simulation Software - Ahmad Shah Hizam, Md. Yasir; N. M. Zuki, N. M. (IOP Publishing, 2018)
In the nowadays-competitive world, efficiencies and the productivity of the assembly line are essential in manufacturing company. This paper demonstrates the study of the existing production line performance. The actual cycle time observed and recorded during the working process. The current layout was designed and analysed using Witness simulation software. The productivity and effectiveness for every single operator are measured to determine the operator idle time and busy time. Two new alternatives layout were proposed and analysed by using Witness simulation software to improve the performance of production activities. This research provided valuable and better understanding of production effectiveness by adjusting the line balancing. After analysing the data, simulation result from the current layout and the proposed plan later been tabulated to compare the improved efficiency and productivity. The proposed design plan has shown an increase in yield and productivity compared to the current arrangement. This research has been carried out in company XYZ, which is one of the automotive premises in Pahang, Malaysia.